MODEL PEMBELAJARAN KEBUGARAN JASMANI BERBASIS PERMAINAN MODIFIKASI PADA SISWA SMP - Fauzi, Dira; Pelana, Ramdan; Samsudin, Samsudin; Sujarwo, Sujarwo (Universitas Hamzanwadi, 2025)
This study examines the effectiveness of a modified game-based physical fitness learning model (MOFIT) for junior high school students through a Research and Development (R&D) approach using the ADDIE model. The study was implemented in three junior high schools in Ciputat District, namely SMP Waskito, SMP Anugerah Abadi, and SMPN 9 Kota Tangerang Selatan, involving 90 students selected through cluster random sampling. Data collection was conducted using adapted physical fitness test instruments (Harvard Step Test, Wall Squat Test, Press-ups Test, Sit and Reach Test) and student/teacher response questionnaires. The research findings showed significant improvements in all targeted physical fitness components: cardiovascular endurance (average decrease of 29.078 bpm, p < .001), muscle strength (average increase of 19.200 seconds, p < .001), muscle endurance (average increase of 7.622 repetitions, p < .001), and flexibility (average increase of 3.002 cm, p < .001). Student responses showed a very high level of acceptance (91.7% approval), with increased enthusiasm (96.7%) and enjoyment (95.6%). Teachers reported the model as adaptable to variations in school facilities. The MOFIT model proved effective in improving physical fitness while facilitating student engagement, offering a viable alternative to conventional methods in physical education.